Impact of mild hypohydration on 100 m front crawl performance and starting block peak force production in competitive university-level swimmers - El Fethi Abed, M.; Deshayes, T. A.; Claveau, P.; Jeker, D.; Thénault, F.; Goulet, E. D. B. (Sports, 2020)
Unstructured, ad libitum drinking may predispose some athletes to start exercise already slightly hypohydrated (decreased body water). The impact of pre-exercise mild hypohydration on subsequent swimming performance is still unknown. Hence, the goal of this study was to examine its effect on peak force production on the starting block and 100 m front crawl swimming performance in competitive university-level swimmers. At least one hour after having been passively exposed to heat where a body mass loss of 1.5% was induced or euhydration (normal body water) maintained, nine participants (age: 22 ± 2 years) underwent an assessment of their peak force production on the starting block and 100 m front crawl performance. One hour following hypohydration, rectal temperature had returned to baseline in each condition. Urine osmolality and specific gravity were higher (p < 0.05) with hypohydration than euhydration (995 ± 65 vs. 428 ± 345 mOsmol/kg; 1.027 ± 0.003 vs. 1.016 ± 0.007 g/mL) prior to exercise testing, as was perceived thirst. Swimming performance (p = 0.86) and peak force production (p = 0.72) on the starting block did not differ between the hypohydration and euhydrated condition (63.00 ± 4.26 vs. 63.09 ± 4.52 s; 1322 ± 236 vs. 1315 ± 230 N). The current results indicate that mild hypohydration, which may occur with ad libitum drinking, does not impede peak force production on the starting block and 100 m front crawl performance in university-level competitive swimmers. Planned drinking is not required prior to such an event.